Problem of mathematical deduction of the existence of black holes - Yuan-Shun Chin (International Journal of Mathematics and Mathematical Sciences)
The mathematical proof of existence of Black Hole is based on the assumption of mass being independent of speed. Considering the effect of special relativity of the dependence of mass with speed there is no Black hole.